Technologies and the prediction of spin bowlers in the game of cricket - ., Mounica; K, Saravanakumar (International Journal of Engineering and Technology, 2019)
Technologies plays an formidable role in any type of sports. In many games it plays the role of trainers for the players to enrich the skills for the competitiveness. It is replacing the umpires for the correct decision making to overcome human error. In the game of cricket, the spin bowling is very important and to study the different methods, efficiency, controlling mechanism, spinning action, direction and rotational speed of the ball. These things can be calculated based on using effective technological tools. In India the cricket highest body, Board of Control for Cricket in India (BCCI) have been using the database for selecting players for any tour-nament and various franchisers in the case of premier leagues in India and other countries. Â Â